Implementasi Kurikulum Merdeka dalam Sekolah Penggerak di SMA Negeri 1 Krian - Nia Amelia Putri; Yulisa Febriani; Anita Jingga Ratna Dewanti; Fitria Nur Sa’idatur Rohmah; Ayu Wulandari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research was conducted with the aim of outlining the challenges that exist in the implementation of the independent curriculum at SMA Negeri 1 Krian, the most important of which is the understanding and implementation of the project to strengthen the Pancasila profile and differentiated learning. The method used in this study is a qualitative research method which uses non-numerical data and does not carry out statistical analysis, conventional. The challenge in implementing the independent curriculum at SMA Negeri 1 Krian is that teachers prepare more media for learning. However, not all teachers are in the creative zone, but some teachers are still in the comfort zone so that learning still uses conventional media. In the implementation of the independent curriculum, there are 2 distinctive features, namely, differentiated learning and the project to strengthen the p5 Pancasila profile. Differentiated learning adapts several student learning needs, for example auditory, kinesthetic, and visual learning styles. In addition, there is a mistake in the P5 goal which should have focused on character development rather than the final product. This study shows the challenges of implementing the independent curriculum which includes teachers providing more learning media. Differentiated learning focuses on the learning needs of students who consider auditory, kinesthetic, and visual learning styles.